In-vitro Inhibition of Mineralisation of Urinary Stone Forming Minerals by Some Medicinal Plant Extracts - Rao, T.V.R.K.; Das, Maitreyee (Asian Journal of Chemistry, 2010)
Extracts of some medicinal plants and shrubs, viz., horse gram (Dolichose biflorus), bark of sal tree (Shorea robusta), leaves of Pathhar chur (Bryophyllum spp.), bark of Ashoka tree (Saraca indica), Brahmi buti (Centella asiatica), leaves of Tulsi (Ocimum sanctum), leaves of Khatmithi (Oxalis spp.) and sticks of Chiraita (Swertia chirata) have been studied as inhibitors in the mineralization of urinary stone forming minerals, viz., calcium phosphate, oxalate or carbonate. Inhibition efficiency has been studied in different experimental models. Utility of the results in urolithiasis inhibition has been discussed.